2022
DOI: 10.3390/cells11182825
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Related Myocardial Fibrosis: Inflammatory Hypothesis and Crucial Role of Immune Cells Dysregulation

Abstract: Although the underlying mechanisms driving human immunodeficiency virus (HIV)-mediated cardiovascular diseases (CVD) onset and progression remain unclear, the role of chronic immune activation as a significant mediator is increasingly being highlighted. Chronic inflammation is a characteristic feature of CVD and considered a contributor to diastolic dysfunction, heart failure, and sudden cardiac death. This can trigger downstream effects that result in the increased release of pro-coagulant, pro-fibrotic, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 106 publications
0
13
0
1
Order By: Relevance
“…The detection of IL-17A-producing CD4 + T-cells in the atherosclerotic plaque of mice [24,6,13,18,20,28,33,81,9496] supports the possibility that subsets of Th17 cells may be recruited into the vascular beds and locally fuel atherosclerosis. In line with this scenario, in our study TPV + compared to TPV − ART-treated PLWH exhibit increased plasma levels of CCL20, a chemokine essential for CCR6 + Th17 cell trafficking [8082].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The detection of IL-17A-producing CD4 + T-cells in the atherosclerotic plaque of mice [24,6,13,18,20,28,33,81,9496] supports the possibility that subsets of Th17 cells may be recruited into the vascular beds and locally fuel atherosclerosis. In line with this scenario, in our study TPV + compared to TPV − ART-treated PLWH exhibit increased plasma levels of CCL20, a chemokine essential for CCR6 + Th17 cell trafficking [8082].…”
Section: Discussionmentioning
confidence: 89%
“…In addition to traditional CVD risk factors (e.g., smoking, hypertension, dyslipidemia, diabetes, insulin resistance, and/or sedentary life-style) [12] and mental health disorders with an impact on CVD risk, HIV-specific mechanism (e.g., HIV-mediated metabolic alterations due to long-term administration of ART) contribute to the premature occurrence of CVD in ART-treated PLWH [7,8,10,[13][14][15]. In addition, the persistence of HIV reservoirs during ART is associated with impaired intestinal mucosal barrier functions, microbial translocation, and immune dysfunction, and chronic inflammation, which, together with CMV and other coinfections, contribute to an increased CVD risk in this group [16][17][18][19][20]. Thus, CVD represents a major non-AIDS co-morbidity in ART-treated PLWH and novel therapeutic interventions are needed to reduce this risk.…”
Section: Introductionmentioning
confidence: 99%
“…47 The mechanistic pathways leading to myocardial remodeling and fibrosis in HIV remain uncertain, but chronic inflammation is likely to play a crucial role. 99,100 Despite HIV viral suppression, residual immune activation and subsequent chronic inflammation persist in PLWH. 101 Chronic HIV infection may represent a perpetuation of the classical remodeling phase of viral myocarditis.…”
Section: Cardiac Remodeling and Fibrosis Phasementioning
confidence: 99%
“…105 It has been postulated that in a state of chronic immune activation, macrophages release profibrotic cytokines, such as IL-10 and TGF-β1 (transforming growth factor-β1), leading to increased collagen I and III deposition and subsequent myocardial fibrosis. 100,102 Linking Inflammation to Myocardial Fibrosis Attempts have been made to establish whether the myocardial fibrosis observed on CMR in PLWH is correlated with markers of inflammation. In a cohort of women living with HIV in the United States without CVD and wellcontrolled HIV, diffuse myocardial fibrosis was not only more prevalent compared with HIV-negative controls but also associated with the macrophage activation marker sCD163 (soluble CD163).…”
Section: Cardiac Remodeling and Fibrosis Phasementioning
confidence: 99%
“… 16 , 17 , 18 , 19 For example, in PLWH1, elevated plasma levels of proinflammatory cytokines can contribute to endothelial dysfunction, fibrotic remodeling, and hypercoagulation. 20 , 21 Although the impact of the dysregulation of bystander cells have been extensively studied in PLWH1, in particular within the field of cardiovascular diseases, 22 less is known about bystander cells in HIV-2 infection. Moreover, we and others have shown that both viremic and aviremic PLWH2 display signs of immune pathology, such as expansion of activated and exhausted CD4 + and CD8 + T-cells, B-cells, natural killer cells (NK-cells), NK T-cells (NKT), monocytes, and dendritic cells (DCs).…”
Section: Introductionmentioning
confidence: 99%